Camel treatment through ages: A comparative study in Veterinary Medicine - Seif, Mohamed Mostafa (Journal of agricultural, environmental and veterinary sciences, 2025)
The research traces the historic trajectory of veterinary practices for the care of camels from its start in written Islamic veterinary tradition to orally transmitted ethnoveterinary knowledge among the Bedouin peoples, to today’s evidence-based veterinary application. It attempts to make, through a critical holistic approach, a diagnostic and therapeutic practice-based comparison of the three epistemic regimes (traditional, folk, and modern) to reflect upon the viability and efficacy of common traditional procedures (such as cauterization, bloodletting, and medicinal use of herbs) through the prism of today’s medical needs. It also reveals the primordial role of Arab-Islamic civilization in creating veterinary science and demonstrates how written and oral knowledge intertwined to form a holistic epistemic system. It identifies, in conclusion, promising practical bases for synthesizing such knowledge by the application of a «One Health» approach to connect the health of humans, animals, and the environment. It sustains such synthesis through technology use, educational activities for populations, as well as intangible medical documentation, and recognizes a sustainable developmental outlook for the healthcare of camels.